Students' Perception Towards Pedagogical and Professional EFL Teacher at Al-Ittihad Islamic Senior High School - Novi Ayu Lestari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract : This research present the students’ perception towards pedagogical and professional EFL Teacher at Al-Ittihad Islamic Senior High School. For being a good teacher, they should know what are included in standard competencies of teacher. The competencies are: (1) Pedagogical Competence, (2) Personality Competence, (3) Social Competence, (4) Professional Competence. This research used descriptive qualitative as the research design. The participants were students of twelfth grade at Al-Ittihad Islamic Senior School, and 10 students were chosen by researcher randomly. The researcher used questionnaire as the instrument for this research to collect the data. The questionnaire is provides 25 statements which was divided into two categories, they are; pedagogical and professional competencies. The data were collected by using online-based questionnaire namely Google Form. The findings of this research showed that more than 7 from 10 student answered that their English teacher often and always explained the materials well, creative in using various method to deliver the materials, always observe students’ behavior in participating in teaching-learning process and can make the atmosphere of learning process conducive keywords: Students' Perception, Pedagogical competence, Professional Competence